8‐Hydroxyquinoline Fluorophore for Sensing of Metal Ions and Anions. Issue 12 (5th November 2020) - Rohini,; Paul, Kamaldeep; Luxami, Vijay
Abstract: Among various known hydroxyquinolines, 8‐hydroxyquinoline (8‐HQ) is the most prevalent moiety due to excellent property for the formation of the complex with different metal ions and anions, and utilized in a wide variety of applications in pharmacological and medicinal fields. 8‐Hydroxyquinoline moiety and its analogues acts as fluorophoric ligands on complex formation with alkali and alkaline as well as transition metal ions and anions, thus, considered as an ideal building block in metallo‐supramolecular chemistry for recognition, separation, and quantitative investigation of cations. 8‐Hydroxyquinoline moiety is also used in various applications for the advancement of novel fluorescent chemosensors in a wide variety of areas viz ., material chemistry, bioorganic chemistry, molecular imaging, analytical chemistry, molecular recognition, medical and biological science communities. The present review emphasises on the progress of sensing properties of 8‐HQ centred small‐molecule fluorescent chemosensors towards several metal ions viz ., Fe 3+, Al 3+, Ag +, Hg 2+, Cu 2+, Pd 2+, Zn 2+, Cr 3+, Cd 2+, Mn 2+, Ca 2+, and K + and anions such as F −, CN − and PPi, from 2008 to 2020, because of their sensitivity and selectivity in terms of diverse colour changes for different species. This critical and comprehensive review might facilitate the improvement of more prevailing chemosensors for future exciting and broad applications. Abstract : The present review represents the progress of sensing properties of 8‐HQ centred small‐molecule fluorescent chemosensors towards several metal ions and anions from 2008 to 2020.